The Influence of Livelihood Assets in Livelihood Resilience Farm Household at Sukabakti Village, Bekasi - Azzahra, Fatimah; Dharmawan, Arya Hadi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
The purpose of this study was to analyze the use of livelihood assets by farm household and their influence o n th e leve l o f fa rm h o u seh o ld ’s res ili en ce a t S u kab a kti villa g e. Fa rm h o u seh o ld wa s d i vid e d in to t wo a rea s that was farm household in the flood area and farm household in the not flood area. In addition, the research also view structure a living that on farm, off farm, and non farm built by farm household in two areas. This study combined quantitative approach using questioner method and qualitative approach using depth interview method. The result of these study explained livelihood asset used by farmers in Sukabakti village highly influencin g th eir resil ien ce ’s le vel. There are significant differences between the two areas where farm household in the flood area are dominated in non farm sector, while in the not flood area are d o m ina ted o n fa rm an d o ff fa rm secto r. T h e lev el o f h o u seho ld ’s resil ien ce in th e n o t flood a rea is h igh er than farm household in the flood area. Keywords: farm household, livelihood assets, resilience